Intercultural and workplace adaptation: a case study of Malaysian professional returnees - Kunasegaran, Mageswari; Ismail, Maimunah; Mohd Rasdi, Roziah; Ismail, Ismi Arif (Elsevier, 2016)
Intercultural adaptation is one of the factors affecting success of returnees’ adaptation at the workplace. This study aims to gain insights into Malaysian professional returnees’ cultural response from the organisational challenges and supportive role perspective. Integrative Communication Theory was used to explain the interaction between returnees and the organisation climate. This study was conducted through a qualitative approach. Thematic analysis revealed two themes: a) challenges in working environment, and b) the supportive role of the management is required in their adaptation. The empirical findings indicate that Malaysian professional returnees experience different challenges in the organisation. Top management support is the most prominent factor that influences returnee's adaptation at the workplace.